180k views
5 votes
Can someone tell me the answer pls

Can someone tell me the answer pls-example-1
User H W
by
4.8k points

1 Answer

3 votes

Explanation:

a normal function expresses y (the functional result) in terms of x (and constants).

we need to transform this to express now x in terms of y (and constants).

at the end we only rename x into y and y into x to make it an actual function.

h(x) = y = (-5x + 6)/(3x + 4)

y(3x + 4) = (-5x + 6)

3xy + 4y = -5x + 6

4y - 6 = -5x - 3xy = x(-5 - 3y)

x = (4y - 6)/(-5 - 3y)

and after renaming we get therefore the function

y = h-1(x) = (4x - 6)/(-3x - 5)

User WEshruth
by
4.4k points